The Routledge Handbook of the Gig Economy - Ness, Immanuel; Ovetz, Robert; Roque, Isabel; Swidler, Eva-Marie; Zwick, Austin (Routledge International Handbooks, 2023)
digital labour; Globalisation; platform economy; platform economy